PTU-004 Safe and Effective Day Case Endoscopic Resection of Giant Colorectal Adenomas Greater than 8CM is Achievable in a Tertiary Referral Unit. (17th August 2016) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: There are few reports on the management of very large sessile colorectal polyps in western practice. Endoscopic resection of these lesions can be technically challenging and they have traditionally been subjected to surgical resection in western centres. Our aim was to determine the safety and effectiveness of endoscopic resection of giant colorectal polyps in a tertiary referral interventional endoscopy unit. Methods: All lesions were assessed with magnification chromoendoscopy. Patients with colorectal polyps greater than or equal to 8 cm deemed suitable for endoscopic resection were included. Several techniques were employed including piecemeal endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), and hybrid techniques involving EMR, ESD, transanal resection or transanal endoscopic microsurgery (TEMS). All patients underwent surveillance magnification chromoendoscopy at 3 and 12 months. Results: 88 lesions greater than or equal to 8 cm were resected with a median size of 10 cm (range 8 cm-16cm). Mean age was 74 years. 49 lesions were in the rectum or rectosigmoid, 13 in the right colon and 27 in the descending and sigmoid colon. There were 6 tubular adenomas, 73 tubulovillous adenomas, 7 adenocarcinomas and 1 sessile serrated adenoma. The recurrence rate was 17%, 64% detected at the first surveillance endoscopy and 36% later recurrences. Of these, 2 patients required surgery in the form of TEMS and a right hemicolectomy, 1 died of unrelated causes, and the rest were managed with a repeat endoscopic resection and were free from recurrence at last surveillance. There were no clinically significant perforations. 3 perforations were closed with endoscopic clips and managed conservatively without complications. There were 2 unplanned admissions for bleeding which did not require further intervention. The recurrence and complication rate were significantly higher than for adenomas smaller than 8 cm. 72% were successfully completed as day cases. Of those patients without invasive cancer at their initial resection and alive at last follow up, 93% avoided surgery and were free from recurrence. Conclusion: Successful endoscopic resection of giant colorectal adenomas is achievable in a western setting with a low risk of complications. In our series, none of 49 patients with rectal or rectosigmoid lesions, who would have traditionally required an anterior resection or abdominoperineal excision, required a major surgical resection. Almost all patients with benign polyps were successfully treated endoscopically and avoided surgery. Nonetheless, it is associated with a higher risk of complications and recurrence compared with lesions less than 8 cm and therefore should be considered in specialist units. Disclosure of Interest: None Declared